A Study on the Fabrication of a Textured Cutting Tool using a Plasma Focus Machine - Teh, Thiam Oun; Singh, Arwinder; Ali, Jalil; Heoh, Saw Sor; Lee, Sing (INTI International University, 2018)
In this paper, a study on the possibility of producing a textured cutting tool using the nitriding effects of a 3 kJ Mather-type dense plasma focus device (DPF) in a low-pressure nitrogen atmosphere is carried out using the INTI International University plasma focus machine. It has been found that the INTI International University plasma focus machine can be used to provide the hardening effect to steel as well as imparting a suitable surface texture to the steel thus enabling it to become a textured cutting tool for the machining of aluminium products.